Julia high performance : optimizations, distributed computing, multithreading, and GPU programming with Julia 1.0 and beyond /: optimizations, distributed computing, multithreading, and GPU programming with Julia 1.0 and beyond. (2019) - Sengupta, Avik
No abstract available